2021
DOI: 10.1186/s12891-021-04173-0
|View full text |Cite
|
Sign up to set email alerts
|

Urdu version of Oswestry disability index; a reliability and validity study

Abstract: Background Oswestry Disability Index (ODI) is broadly used in clinical and research settings for assessing the disability level in patients with lumbar radiculopathy but it has not been translated into Urdu language according to the pre-established translation guidelines as well as the validity and reliability of ODI Urdu version has not been tested yet. The aim of this study was to translate ODI in native Urdu language (ODI-U) according to recommended guidelines and to measure its psychometric… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 73 publications
0
11
0
Order By: Relevance
“…The inter-item correlation was also computed. The alpha value for inter-item correlation > 0.7 is assumed to be good [ 41 ]. To ensure that the patient’s state changed as little as possible, the current study used a three-day gap, similar to prior studies that used fewer test-retest intervals [ 3 , 22 , 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…The inter-item correlation was also computed. The alpha value for inter-item correlation > 0.7 is assumed to be good [ 41 ]. To ensure that the patient’s state changed as little as possible, the current study used a three-day gap, similar to prior studies that used fewer test-retest intervals [ 3 , 22 , 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Amjad F et al, [26] reported that ODI was considered to be a gold standard self-reported outcome measure tool to evaluate quality of life and disability level after lumber radiculopathy.…”
Section: Discussionmentioning
confidence: 99%
“…VAS is one of the most commonly used index to measure the degree of pain 27 and ODI is a condition‐specific outcome measure for spinal disorders. 28 …”
Section: Methodsmentioning
confidence: 99%